Arte, sinestesia e comida: experiência sensorial na exposição Cidade da Língua, um estudo de caso - Guarreschi, Lara Mazeto [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This study aims to present a theoretical study of the relations that manifest themselves between Art and Food, especially by the synesthetic approach of the theme, and with a case study, in particular, of the exhibition City of Tongue by Bompas & Parr, which we understand, as the result of the numerous initiatives that historically preceded it. To this end, it has been conducted a bibliographic and documentary survey, as well as a methodical analysis based on experience of the exhibition, establishing synesthetic binding relationships between food and art, as well as historical path between art and food. Considering these characteristics and reflections, we shall seek an approximation and interaction of art with food that dialogues with senses, both with perspectives of application in education, as well as in the commercial and academic scope, in future research

O objetivo deste trabalho é realizar um estudo teórico das relações que se manifestam entre a Arte e a Comida, especialmente pela abordagem sinestésica do tema, e com um estudo de caso, em particular, da exposição Cidade da Língua de Bompas & Parr, que entendemos ser decorrência das inúmeras iniciativas que historicamente a precederam. Para tanto, realizamos um levantamento bibliográfico e documental, bem como uma análise, metódica e calcada em relato de experiência da exposição, estabelecendo relações vinculativas sinestésicas entre a comida e a arte, bem como trajeto histórico entre arte e alimentação. Com essas características e reflexões, buscar-se-á uma aproximação e interação da arte com a comida que dialoga com sentidos, tanto com perspectivas de aplicação na educação, como no âmbito comercial e acadêmico, em futuras pesquisas
Keywords: Arte moderna; Culinária na arte; Artes; Cooking in art